Perancangan Aplikasi Pemantauan Peserta Magang Di PT Telkom Indonesia Tbk Kota Banjar Dengan Laravel - Depa Melina; Maulana, Haisyam; Maulani, Shanti; Laia, Firdaus (Jurnal Sistem Informasi Galuh, 2023)
PT. Telkom Indonesia, Tbk Banjar City or referred to as Datel (Daerah Telkom) Banjar is one part of Telkom Tasikmalaya which directly communicates with consumers in the Banjar City area, both in terms of maintenance and installation of new telecommunications services. Datel Banjar is a place that is usually chosen by students majoring in IT to conduct internship programs (PKL). The application of technology in monitoring the internship program is considered necessary, because previously all internship activities were carried out manually, such as when filling out attendance and other things. However, there are several obstacles, including that the supervisor cannot check the attendance of participants every day and the participants' daily activities become uncontrolled. The research outlined in this Final Project aims to correct the shortcomings of the internship program management system at Datel Banjar. The method used in this study is the waterfall method from the System Development Life Cycle. This website-based application using Laravel was created to facilitate the process of running the internship program at Datel Banjar, where supervisors can easily monitor the attendance and daily activities of each participant. In addition, participants are also facilitated in reporting attendance and daily activities to the supervisor.